FEHAT: efficient, large scale and automated heartbeat detection in Medaka fish embryos - Ferreira, Márcio Soares; Stricker, Sebastian; Fitzgerald, Tomas; Monahan, Jack; Defranoux, Fanny; Watson, Philip; Welz, Bettina; Hammouda, Omar; Wittbrodt, Joachim; Birney, Ewan (Bioinformatics, 2024)
High-resolution imaging of model organisms allows the quantification of important physiological measurements. In the case of fish with transparent embryos, these videos can visualize key physiological processes, such as heartbeat. High throughput systems can provide enough measurements for the robust investigation of developmental processes as well as the impact of system perturbations on physiological state. However, few analytical schemes have been designed to handle thousands of high-resolution videos without the need for some level of human intervention. We developed a software package, named FEHAT, to provide a fully automated solution for the analytics of large numbers of heart rate imaging datasets obtained from developing Medaka fish embryos in 96-well plate format imaged on an Acquifer machine. FEHAT uses image segmentation to define regions of the embryo showing changes in pixel intensity over time, followed by the classification of the most likely position of the heart and Fourier Transformations to estimate the heart rate. Here, we describe some important features of the FEHAT software, showcasing its performance across a large set of medaka fish embryos and compare its performance to established, less automated solutions. FEHAT provides reliable heart rate estimates across a range of temperature-based perturbations and can be applied to tens of thousands of embryos without the need for any human intervention.Data used in this manuscript will be made available on request.
Veröffentlicht: 07. November 2024
Gesehen am 11.03.2025